A comparison of the spectral properties of high temperature annealed long period gratings inscribed by fs laser, uv and fusion-arc - Kalli, Kyriacos; Allsop, Thomas P.; Webb, David J. (My University, 2006)
Long period gratings have been inscribed in standard single mode fibre using a fs laser system, a fusion arc and a UV laser and a comparative study carried out of their thermal behaviour. The fs laser induced gratings can survive temperatures in excess of 800°C, however the inscription process can induce considerable birefringence within the device. Annealing studies have been carried out showing that below 600°C, all three grating types show a blue shift in their room temperature resonance wavelengths following cyclic heating, while above 600°C, the UV and arc induced LPGs exhibit a red shift, with the fs LPG showing an even stronger blue shift. High temperature annealing is also shown to considerably reduce the birefringence induced by the fs inscription process.
Keywords: Liquefied petroleum gas; Resonance; Spectrum analysis; Diffraction gratings